Sejarah Perkembangan Reog Sepuh di Paguyuban Singo Gaplok Kabupaten Ponorogo - Apriyanto, Sendi Iman; Wibowo, Anggono Kusumo (Gesture: Jurnal Seni Tari, 2025)
This research examines the development of Reog Sepuh in Bedingin Village, Sambit District, Ponorogo Regency as a form of cultural heritage that has evolved within the dynamics of social changes. The research focuses on the transformation of performance structure, philosophical values, and preservation efforts carried out by its supporting community. This research employs a qualitative approach with ethnographic methods, participatory observation, in-depth interviews, and document study. The results show that Reog Sepuh Bedingin has uniqueness in terms of performance structure, movement patterns, and ritual functions that are still maintained to this day. Despite facing the challenges of modernization and shifting interests of the younger generation, Reog Sepuh Bedingin persists through regeneration efforts, creative innovations that still respect traditional standards, and support from local government and community. This research emphasizes the importance of balance between preserving authentic values and contextual adaptation to ensure the sustainability of traditional arts in the modern era.